Effect Of Varying Dietary Protein Levels In Snakehead Broodstock, Channa Striata (Bloch, 1793) On Egg, Larval Quality, Digestive Enzyme Activity And Ontogenic Development Of The Digestive Tract - Manogoran, Janaranjani (2016)
The present study was carried out to determine the quality of eggs and larvae from channa striata broodstock that were fed different levels of dietary protein. C. Striata juveniles (mean weight 54.5 ± 2.6 g) were randomly selected and stocked in 4m x lm x im (length x width x depth) canvas tanks at adensity of 60 fishes per tank in triplicates for each treatment. Four experimental diets containing varying protein levels (350, 400, 450 and 500 g kg'1) were formulated and fed twice daily to satiation, at 10:00 a.M. And 17:00 p.M. For 6 months until spawning. After six months on the experimental diets, matured male and female brood fish were randomly selected for artificial spawning at the ratio of 1: 1. A series of two experiments were conducted to achieve the objectives of this cunent study. First, the quality of eggs and larvae were assessed based on biometric of egg and larvae, egg lysozyme, tolerance of larvae to starvation, tolerance to stress triggers such as temperature and ph and amino acid content.